2009
DOI: 10.4171/rsmup/122-8
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Two-Step Nilpotent Lie Groups Relative to Multicontact Structures

Abstract: -Let fX i ; Y k g denote a fixed basis of the Lie algebra n of a connected and simply connected nilpotent Lie group N of step two. Under a technical assumption on fX i ; Y k g, we prove that the Lie algebra w of vector fields V on N that satisfy [V ; X i ] l i X i is finite dimensional, a property that we refer to as rigidity. Our proof allows the explicit count of dim w.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In [9] it is shown that a large class of nonrigid examples exists. As for multicontact structures, the reader is referred to [3,4,6,8,13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In [9] it is shown that a large class of nonrigid examples exists. As for multicontact structures, the reader is referred to [3,4,6,8,13,14,16].…”
Section: Introductionmentioning
confidence: 99%